A Statistical Analysis of Internet Based ICT adoption among SMEs in India: Drivers and Challenges - Kayalvizhi, S.; Gunasekar, T.; Thenmozhi, S. (IJRDO - Journal of Applied Management Science, 2016)
The purpose of this study is to explore the key drivers and challenges of Information and CommunicationTechnologies (ICTs) adoption by Small and Medium Sized Enterprises (SMEs) in India. SMEs play a majorrole in developing and developed economies in job creation and diversification of economic activities. Theliterature shows that while there are many drivers of ICTs adoption by SMEs, there are equally manychallenges from various factors. SMEs that effectively utilize ICTs can compete efficiently in both domestic andglobal arenas. Understanding the drivers, and challenges to ICT adoption by SMEs especially in thedeveloping countries like India have not been addressed adequately. This study attempt to address this gap. Asurvey questionnaire was used to collect data from 250 different SMEs in India. Quantitative approaches wereused for data analyses. The study identified the key challenges to ICT adoption as lack of internal capabilities,high cost of ICTs, poor infrastructure, financial constraints and lack of information about suitable ICT solutionsand lack of time to implement. The study also identified the key drivers of ICT adoption as the desire to increasecustomer service and responsiveness, increase ability to compete, improve overall communication, increasesales and profit and to have better access to information. The result of the study will be beneficial to current andfuture SMEs in India.